Challenges facing general education teachers in inclusive classrooms in Qatar - Jabri, Alanood; Alodat, Ali M.; Al-Hendawi, Maha; Ianniello, Annalisa (Frontiers in Education, 2025)
Inclusive education has emerged as a growing national priority in Qatar, reflecting both international obligations and the strategic goals of the Qatar National Vision 2030. Despite this commitment, the effective implementation of inclusive practices remains constrained by persistent challenges encountered by general education teachers. This study examines the nature and extent of these challenges and investigates the impact of teacher demographic variables on inclusive teaching practices. Employing a mixed-methods design, quantitative data were collected from 203 teachers through a validated survey instrument, while qualitative insights were gathered via structured interviews with five general education teachers. Data were analyzed using SPSS 29 for quantitative analysis and ATLAS.ti 25 for thematic interpretation. The findings indicated a moderate level of challenges across cognitive, administrative, psychological, and social domains. Notably, no statistically significant differences were observed in teacher demographics. Thematic analysis revealed two central themes: enhancing inclusive education and promoting social integration. By foregrounding the experiences of general education teachers, this study addresses a critical gap in the literature. It underscores the need for sustained professional development, curricular adaptation, and institutional support to bridge the disconnect between inclusive policy frameworks and classroom realities.